STRATEGI KOMUNIKASI IKATAN WANITA GEMUK INDONESIA SEBAGAI WADAH MOTIVASI WANITA PLUS SIZE - Yolanda Stellarosa; Desy Iwanti (Communicology: Jurnal Ilmu Komunikasi, 2017)
Media Features beautiful as an ideal body shape which is slim, not fat with a flat stomach.Ã‚ There are various beauty concepts which have been adopted by the mass media which stick in the public's mind. This often leads to acts of discrimination and bullying, which happened to a plus body size woman. Plus size women federation community (KAGUMI) has become a place for self expression and help for women of plus size to increase their confidence. This research aims to determine the communication strategy of Kagumi as a place to motivate and increase self confidence of their members. This research uses qualitative method; interviewees are the founder and members of Kagumi. The data obtained were analyzed using interactive analysis techniques including reduction, data presentation and conclusion. Results of this research show that the community role of Kagumi is a place to motivate through a credible communicator in conveying motivational messages can be quotes, words of wisdom which contain positive values for life, using inspirational stories through social media facebook, television, tabloids and offline activities. Obstacles encountered in the implementation of the communication strategy are self control from members, cyber crime and the spread of the message on a large scale in media which is contrary to the purpose of Kagumi.